Application of interval analysis for improving reliability of estimation of hardness value spread for nuclear structural materials - Yefimov, A.V.; Potanina, Т.V. (Вопросы атомной науки и техники, 2020)
The applications of the interval and standard probabilistic approaches for verifying the reliability of the results of an experiment studying the mechanical properties of nuclear materials are compared. The presence of “outliers” in a sample of hardness values for hafnium ingots is studied with for fixed oxygen mass content. The situation of measurement error limitation without reliable information about its distribution is considered. The correctness of the application of numerical methods of interval analysis for processing experimental data under conditions of uncertainty and noisy experimental data is shown. Проведено порівняльний аналіз застосування інтервального і стандартного ймовірнісного підходів для перевірки достовірності результатів експерименту з вивчення механічних властивостей ядерних матеріалів. Досліджується вибірка значень твердості зразків злитків гафнію при однаковому масовому вмісті кисню на наявність промахів спостережень. Розглядається ситуація обмеженості похибки вимірювань без достовірної інформації про її розподіл. Показана коректність застосування чисельних методів інтервального аналізу для обробки експериментальних даних в умовах невизначеності і наявності «шуму» в експериментальних даних. Проведен сравнительный анализ применения интервального и стандартного вероятностного подходов для проверки достоверности результатов эксперимента по изучению механических свойств ядерных материалов. Исследуется выборка значений твердости образцов слитков гафния при одинаковом массовом содержании кислорода на наличие промахов наблюдений. Рассматривается ситуация ограниченности погрешности измерений без достоверной информации о ее распределении. Показана корректность применения численных методов интервального анализа для обработки экспериментальных данных в условиях неопределенности и зашумленности экспериментальных данных.